1994
DOI: 10.1055/s-0038-1648990
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Platelets Are Less Reactive than Adult Platelets to Physiological Agonists in Whole Blood

Abstract: SummaryPrevious studies have reported that the platelets of healthy term neonates have either diminished or normal reactivity compared to the platelets of adults. To circumvent the methodologic problems of previous studies, we used a whole blood flow cytometric method to study neonatal platelet reactivity to thrombin, a combination of ADP and epinephrine, and U46619 (a stable thromboxane A2 analogue). Inclusion in the assay of the peptide GPRP (an inhibitor of fibrin polymerization) enabled us to study platele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
94
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 48 publications
11
94
0
1
Order By: Relevance
“…In contrast, it has been reported that neonatal platelets are hyporeactive upon in vitro stimulation on the first days after delivery (14,48,51,52), with normalization by at least 10 d after delivery (53). Preanalytical aspects of our study deserve consideration because these could affect the results we have obtained.…”
Section: Discussionmentioning
confidence: 68%
“…In contrast, it has been reported that neonatal platelets are hyporeactive upon in vitro stimulation on the first days after delivery (14,48,51,52), with normalization by at least 10 d after delivery (53). Preanalytical aspects of our study deserve consideration because these could affect the results we have obtained.…”
Section: Discussionmentioning
confidence: 68%
“…In the presence of signifi cant bleeding, immediate reversal using fresh frozen plasma (FFP) or prothrombin complex concentrates or recombinant factor VIIa may be required. 182,183 This hyporeactivity of neonatal platelets is the result of a defect intrinsic to neonatal platelets. 182,183 Paradoxically, the bleeding time is short in newborns because of increased RBC size, high hematocrit levels, and increased levels of multimeric forms of von Willebrand factor.…”
Section: Treatment Of Vka-induced Bleedingmentioning
confidence: 99%
“…182,183 This hyporeactivity of neonatal platelets is the result of a defect intrinsic to neonatal platelets. 182,183 Paradoxically, the bleeding time is short in newborns because of increased RBC size, high hematocrit levels, and increased levels of multimeric forms of von Willebrand factor. [184][185][186] The bleeding time was prolonged, relative to adults, throughout childhood in two of three studies.…”
Section: Treatment Of Vka-induced Bleedingmentioning
confidence: 99%
“…Для осуществления этого ре-жима требуется образец крови в объеме 0,2 мл. CPA используется в неонатологии для исследования пупо-винной и венозной крови новорожденных [51][52][53][54]. На-стоящее исследование было проведено с целью оценки функции тромбоцитов крови новорожденных на CPA, родившихся от матерей с заболеваниями, которые могут оказать влияние на неонатальный гемостаз.…”
Section: гсд и нарушения гемостазаunclassified